Construct validity of the Menopause Rating Scale in Indonesia. (3rd September 2019) - Dwi Susanti, H.; Chang, P.C.; Chung, M.H.
Abstract: Objective : This study assessed the construct validity of the Menopause Rating Scale (MRS) in Indonesia. Methods : The study included 240 women aged over 45 years in Indonesia. The MRS measures psychological, somatic-vegetative, and urogenital symptoms using 11 items obtained from participants' daily symptom records. The intraclass correlation coefficient (ICC) and Cronbach's alpha coefficient were measured to examine the test–retest reliability and internal consistency reliability. The test–retest reliability was evaluated by an extra 30 participants twice at 2-week intervals. For construct validity, exploratory factor analysis (EFA) was employed to assess factor structure and confirmatory factor analysis (CFA) was used to evaluate the structural model fit of the MRS. Results : The ICC for the test–retest reliability ranged between 0.90 and 0.95. The Cronbach alpha coefficients in the somatic-vegetative, psychological, and urogenital dimensions were 0.92, 0.93, and 0.95, respectively. The Kaiser–Meyer–Olkin value was 0.96, and the Bartlett's test of sphericity was statistically significant and adequate for EFA. CFA was tested using the second-order model with three first-order factors and yielded an excellent model fit. Conclusion : Results indicated that the brief questionnaire of the MRS possesses acceptable construct validity for evaluating menopause symptoms in Indonesian women.